Dead is the new black / 1. - Perez, Marlene (Perez, Marlene. Dead is., 2008)
Seventeen-year-old Daisy Giordano, daughter and sister of psychics, attempts to help her mother discover who is behind a series of bizarre attacks on teenage girls in their little town of Nightshade, California.